Ambient mixing ratios of atmospheric halogenated compounds at five background stations in China. (July 2017) - Zhang, Gen; Yao, Bo; Vollmer, Martin K.; Montzka, Stephen A.; Mühle, Jens; Weiss, Ray F.; O'Doherty, Simon; Li, Yi; Fang, Shuangxi; Reimann, Stefan
Abstract: High precision measurements of three chlorofluorocarbons (CFCs), three hydrochlorofluorocarbons (HCFCs), six hydrofluorocarbons (HFCs), three perfluorocarbons (PFCs), and sulfur hexafluoride (SF6 ) were made at five Chinese background stations from January 2011 to December 2012. Their station means in the background air were 239.5 ± 0.69 parts-per-trillion dry-air mole fraction mixing ratios (ppt) for CFC-11, 536.5 ± 1.49 ppt for CFC-12, 74.66 ± 0.09 ppt for CFC-113, 232.1 ± 4.77 ppt for HCFC-22, 23.78 ± 0.29 ppt for HCFC-141b, 22.92 ± 0.42 ppt for HCFC-142b, 11.75 ± 0.43 ppt for HFC-125, 71.32 ± 1.35 ppt for HFC-134a, 13.62 ± 0.43 ppt for HFC-143a, 9.10 ± 1.26 ppt for HFC-152a, 25.45 ± 0.1 ppt for HFC-23, 7.28 ± 0.48 ppt for HFC-32, 4.32 ± 0.03 ppt for PFC-116, 0.63 ± 0.04 ppt for PFC-218, 1.36 ± 0.01 ppt for PFC-318, and 7.67 ± 0.03 ppt for SF6, respectively, which were comparable with those measured at the two Northern Hemisphere (NH) AGAGE stations: Mace Head, Ireland (MHD) and Trinidad Head, California, USA (THD). Compared with our results for earlier years from in-situ measurement at SDZ, background-air mixing ratios of CFCs are now declining, while those for HCFCs, HFCs, PFCs, and SF6 are still increasing. The ratios of the number of sampling events in which measured mixing ratios were elevated above background (pollution events) relative to the total sample frequency (POL/SUM) for CFCs, HCFCs, and HFCs were found to be station dependent, generally LAN > SDZ > LFS > XGL > WLG. The enhancement (△, polluted mixing ratios minus background mixing ratios) generally show distinct patterns, with HCFCs (40.7–175.4 ppt) > HFCs (15.8–66.3 ppt)> CFCs (15.8–33.8 ppt)> PFCs (0.1–0.9 ppt) at five stations, especially for HCFC-22 ranging from 36.9 ppt to 138.2 ppt. Combining with the molecular weights, our findings imply biggest emissions of HCFCs in the regions around these Chinese sites compared to HFCs and CFCs, while the smallest of PFCs, consistent with CFCs being phased out and replaced with HCFCs in China. In addition, relative emission strengths (emission was expressed by mole fractions) of these halocarbons in China were inferred as HCFC-22 > HCFC-141b > HFC-134a > HCFC-142b for the Yangtze River Delta (YRD) and as HCFC-22 > HCFC-142b > HCFC-141b ≈ HFC-134a in the North China Plain (NCP). Graphical abstract: Highlights: Atmospheric halogenated compounds were measured at five stations in China. Mixing ratios were distinguished as in polluted and background air, respectively. Background mixing ratios were comparable with those at two AGAGE stations. In China, background CFCs are declining while increased for other compounds.